Brain distribution of dipeptide repeat proteins in frontotemporal lobar degeneration and motor neurone disease associated with expansions in C9ORF72 - Davidson, Yvonne S (Acta Neuropathol Commun, 2014)
A hexanucleotide (GGGGCC) expansion in C9ORF72 gene is the most common genetic change seen in familial Frontotemporal Lobar Degeneration (FTLD) and familial Motor Neurone Disease (MND). Pathologically, expansion bearers show characteristic p62 positive, TDP-43 negative inclusion bodies within cerebellar and hippocampal neurons which also contain dipeptide repeat proteins (DPR) formed from sense and antisense RAN (repeat associated non ATG-initiated) translation of the expanded repeat region itself. ‘Inappropriate’ formation, and aggregation, of DPR might therefore confer neurotoxicity and influence clinical phenotype. Consequently, we compared the topographic brain distribution of DPR in 8 patients with Frontotemporal dementia (FTD), 6 with FTD + MND and 7 with MND alone (all 21 patients bearing expansions in C9ORF72) using a polyclonal antibody to poly-GA, and related this to the extent of TDP-43 pathology in key regions of cerebral cortex and hippocampus. There were no significant differences in either the pattern or severity of brain distribution of DPR between FTD, FTD + MND and MND groups, nor was there any relationship between the distribution of DPR and TDP-43 pathologies in expansion bearers. Likewise, there were no significant differences in the extent of TDP-43 pathology between FTLD patients bearing an expansion in C9ORF72 and non-bearers of the expansion. There were no association between the extent of DPR pathology and TMEM106B or APOE genotypes. However, there was a negative correlation between the extent of DPR pathology and age at onset. Present findings therefore suggest that although the presence and topographic distribution of DPR may be of diagnostic relevance in patients bearing expansion in C9ORF72 this has no bearing on the determination of clinical phenotype. Because TDP-43 pathologies are similar in bearers and non-bearers of the expansion, the expansion may act as a major genetic risk factor for FTLD and MND by rendering the brain highly vulnerable to those very same factors which generate FTLD and MND in sporadic disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2051-5960-2-70) contains supplementary material, which is available to authorized users.